Plasma metabonomics of classical swine fever virus-infected pigs - Liao, Jiedan; Hu, Wenshuo; Wang, Weijun; Wang, Xinyan; Yu, Shu; Niu, Xinni; Zhu, Wenhui; Zhou, Bolun; Song, Yiwan; Zeng, Weijun; Lu, Zhimin; Chen, Jinding (Frontiers in Veterinary Science, 2023)
Classical swine fever (CSF) is an infectious disease caused by Classical swine fever virus (CSFV), which is characterized by depression, high fever, extensive skin bleeding, leukopenia, anorexia, alternating constipation, and diarrhea. Hemorrhagic infarction of the spleen is the main characteristic pathological change following CSFV infection. Large-scale outbreaks of CSF are rare in China and are mainly distributed regionally. The clinical symptoms of CSF are not obvious, and show variation from typical to atypical symptoms, which makes diagnosis based on clinical symptoms and pathology challenging. In recent years, the incidence of CSF-immunized pig farms in China has increased and new CSFV gene subtypes have appeared, posing new challenges to the prevention and control of CSF in China. Changes in metabolites caused by viral infection reflect the pathogenic process. Metabonomics can reveal the trace metabolites of organisms; however, plasma metabonomics of CSFV-infected pigs have rarely been investigated. Therefore, we used an established pig CSFV infection model to study changes in plasma metabolites. The results showed significant differences in forty-five plasma metabolites at different time periods after CSFV infection in pigs, with an increase in twenty-five metabolites and a decrease in twenty metabolites. These changed metabolites were mainly attributed to the tricarboxylic acid cycle, amino acid cycle, sugar metabolism, and fat metabolism. Thirteen metabolic pathways changed significantly in CSFVinfected pigs, including tricarboxylic acid cycle,inositol phosphate metabolism,glycine, serine and threonine metabolism,lysine degradation,alanine, aspartate and glutamic acid metabolism,pantothenate and CoA biosynthesis,β-alanine metabolism,lysine degradation,arginine and proline metabolism,glycerolipid metabolism,phenylalanine metabolism,arachidonic acid metabolism,linoleic acid metabolism. Among these, changes in fatty acid biosynthesis and Plasma Metabonomics of CSFV-Infected Pigs 2 metabolism occurred at all time periods post-infection. These results indicate that CSFV infection in pigs could seriously alter metabolic pathways.